Design and Development of An Instrumented Knee Joint for Quantifying Ligament Displacements - Cui, Lei; Dale, B.; Allison, Garry; Li, M. (ASME, 2021)
Recently, robotic assistive leg exoskeletons have gained popularity because an increased number of people crave for powered devices to run faster and longer or carry heavier loads. However, these powered devices have the potential to impair knee ligaments. This work was aimed to develop an instrumented knee joint via rapid prototyping that measures the displacements of the four major knee ligaments—the anterior cruciate ligament (ACL), posterior crucial ligament (PCL), medial collateral ligament (MCL), and lateral collateral ligament (LCL)—to quantify the strain experienced by these ligaments. The knee model consists of a femur, lateral and medial menisci, and a tibia-fibula, which were printed from three dimensional (3D) imaging scans. Nonstretchable cords served as main fiber bundles of the ligaments with their desired stiffnesses provided by springs. The displacement of each cord was obtained via a rotary encoder mechanism, and the leg flexion angle was acquired via a closed-loop four-bar linkage of a diamond shape. The displacements were corroborated by published data, demonstrating the profiles of the displacement curves agreed with known results. The paper shows the feasibility of developing a subject-specific knee joint via rapid prototyping that is capable of quantifying the ligament strain via rapid prototyping.